(untitled) (Aintelia Science Notes, 2025)
Sub-Saharan Africa (SSA) hosts approximately 600 million people without electricity access, and solar PV battery mini-grids are the most cost-effective pathway for rural electrification in low-density communities beyond economic reach of grid extension. However, the overwhelmingly inverter-based generation composition of PV-battery mini-grids creates power system stability challenges: conventional gridfollowing (GFL) inverters require an external voltage and frequency reference that is absent during grid-off conditions, precluding black-start and stable islanded operation. Grid-forming (GFM) inverter control architectures which independently establish and regulate voltage and frequency are essential for reliable standalone mini-grid operation. This paper presents a droop-based GFM inverter control implementation with black-start capability, virtual impedance, and load-sharing coordination for a 48 kWp PV/100 kWh lithium-ion battery mini-grid supplying an off-grid community of 320 households in Tambacounda, Senegal. MATLAB/Simulink simulation and hardware-in-the-loop (HIL) validation on a CHIL test bench confirm: voltage magnitude regulation within ±1.5% (1σ), frequency deviation below ±0.3 Hz during cold-load pickup, black-start sequence completion in 380 ms, and reactive load sharing error below 8% between parallel inverters. The architecture provides a replicable technical baseline for GFM mini-grid deployments across SSA.